Perancangan Dan Implementasi Sistem Informasi Antrian Pelayanan Administrasi Kepegawaian Berbasis Web Pada BKPSDMD Kota Jambi - Dio Andrianto Khispan; Nurhadi; Effiyaldi (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2025)
Effective and efficient administrative services are essential elements in supporting the performance of government agencies. However, the manual queuing system still used at BKPSDMD Kota Jambi faces several challenges, such as unstructured queues, long waiting times, and a lack of visitor comfort. This study aims to design and implement a web-based queuing information system to improve service efficiency and quality. This research applies the Waterfall system development method, which includes planning, analysis, design, implementation, and testing phases. The system was designed using Unified Modeling Language (UML) tools, such as use case diagrams, activity diagrams, and Entity Relationship Diagrams (ERD). The system implementation utilized the Laravel framework for the backend, MySQL for the database, and Bootstrap for the user interface. The results indicate that the web-based queuing information system effectively manages queues in a structured manner, provides real-time waiting time information, and enhances visitor comfort during the service process. The system has been successfully implemented at BKPSDMD Kota Jambi, improving the efficiency of administrative services, ensuring a more organized service process, and providing a better experience for service users.